Agricultural productivity in Burkina Faso: The role of gender and risk attitudes - Mohammad H. Sepahvand (Lund University, School of Economics and Management, Department of Economics, 2022)
This study analyzes how risk attitudes influence the agricultural productivity of men and women in a subSaharan African country, Burkina Faso. By using a large representative panel survey of farmers, the results show that as female farmers increase risk taking, the productivity of female-owned plots goes down. The study controls for various socio-economic factors and explores how the diversity of the regions of the country affects gender differences. Findings show that agricultural policy interventions in Burkina Faso need to be gender sensitized when addressing issues related to credit constraints, improved inputs, and policies that support increase in productivity.
Keywords: D13; D81; J16; O13; Q12; Q18; 330; risk attitudes; gender differences; agriculture; productivity; sub-Saharan Africa; Burkina Faso